Novel application of amphiphilic block copolymers in Pickering emulsions and selective recognition of proteins. (30th January 2018) - Xu, Jiangfeng; Sun, Yanhua; Chen, Jian; Zhong, Shian
Abstract : An amphiphilic block copolymer stabilized Pickering high internal phase emulsions and was mildly exfoliated to improve imprinting efficiency. Abstract : Pickering high internal phase emulsions (HIPEs) stabilized by the amphiphilic block copolymer polystyrene–polymethacrylic acid (PS–PMAA) were prepared, and porous materials with specific imprinting sites for the template protein were fabricated after the polymerization of dopamine in the water phase. To the best of our knowledge, PS–PMAA was used for the first time in Pickering emulsion polymerization and removed for the purpose of improving the mass-transfer efficiency. SEM was employed to observe the porous structure. Additionally, FT-IR spectroscopy proved that PS–PMAA was completely removed from the imprinted porous materials. The results indicated that the polydopamine imprinted materials (PDA-MIPs) exhibited an excellent recognition capacity. A high maximum absorption capacity of 472 mg g −1 was obtained, which was 3.07 times higher than that of the non-imprinted polymers (PDA-NIPs). Selective analysis indicated that PDA-MIPs showed a higher selectivity to the template protein when compared to control proteins. The regeneration measurement revealed that the PDA-MIPs could be recycled and remained stable during their reuse.